Clinical Outcomes of Guided Tissue Regeneration with Atrisorb Membrane in the Treatment of Intrabony Defects: A 3-Year Follow-Up Study - Sakallioǧlu, U.; Yavuz, Ü.; Lütfioğlu, M.; Keskiner, I.; Açikgöz, G. (Quintessence Publishing Co. Inc., 2007)
In this controlled clinical trial, initial and long-term treatment outcomes of guided tissue regeneration (GTR) were investigated for a synthetic absorbable membrane (Atrisorb) in intrabony defects. Eighteen defects in 16 patients received GTR with Atrisorb (test), with the membrane applied by an indirect method, and 15 defects in 15 patients were treated with open flap debridement (control). Probing pocket depth (PPD), gingival recession (GR), clinical attachment level (CAL), and linear alveolar bone level (ABL) were recorded at baseline and at 1 and 3 years following the treatment procedures and were assessed as the therapeutic outcome parameters. Both groups demonstrated significant PPD reduction and CAL and ABL gain after 1 year. Among these parameters, alterations in PPD and CAL were statistically significantly greater in the test group than the control group 1 year postsurgery. No significant changes were noted in the parameters of the first year between and within the study groups after 3 years. The results suggest that GTR performed with Atrisorb membrane via an indirect application method may provide favorable clinical outcomes for intrabony defects, and these outcomes may be maintained at least as well as open flap debridement over an extended period.